A kinematic analysis of the spine during rugby scrummaging on natural and synthetic turfs - Swaminathan, R.; Williams, J. M.; Jones, M. D.; Theobald, P. S. (Journal of Sports Sciences, 2016)
Artificial surfaces are now an established alternative to grass (natural) surfaces in rugby union. Little is known, however, about their potential to reduce injury. This study characterises the spinal kinematics of rugby union hookers during scrummaging on third-generation synthetic (3G) and natural pitches. The spine was sectioned into five segments, with inertial sensors providing three-dimensional kinematic data sampled at 40 Hz/sensor. Twenty-two adult, male community club and university-level hookers were recruited. An equal number were analysed whilst scrummaging on natural or synthetic turf. Players scrummaging on synthetic turf demonstrated less angular velocity in the lower thoracic spine for right and left lateral bending and right rotation. The general reduction in the range of motion and velocities, extrapolated over a prolonged playing career, may mean that the synthetic turf could result in fewer degenerative injuries. It should be noted, however, that this conclusion considers only the scrummaging scenario.